Psychological Empowerment and Work Engagement as Mediating Roles Between Trait Emotional Intelligence and Job Satisfaction - Gong, Yue; Wu, Yong; Huang, Peng; Yan, Xiaofei; Luo, Zhengxue (Frontiers in Psychology, 2020)
The majority of research indicates that trait emotional intelligence (EI) plays a crucial role in personal well being; however, the deeper mechanisms of this link remain unclear. The study explored the impact of psychological empowerment and work engagement in the link between trait EI and job satisfaction. Female nurses (370) completed the EI Scale, the Psychological Empowerment Scale, the Utrecht Work Engagement Scale, and the Brief Index of Affective Job Satisfaction. The results of structural equation modeling demonstrated that work engagement partially mediated the association between trait EI and job satisfaction. Moreover, the serial one mediator model revealed that trait EI could influence job satisfaction via the serial mediating impact of “psychological empowerment–work engagement.” These results help to a better understanding of the association between these variables and demonstrate that high trait EI may improve occupational well being from emotional perspectives.